Der Biesbosch in der Provinz Nord-Brabant (Niederlande): Die Landschaftsentwicklung und die Planungsaufgaben in einem Süßwassergezeitendelta - Zonneveld, Izaak Samuel (ERDKUNDE, 1957)
Before 1421 the Zuidhollandse Waard was situated in the southern part of Holland on the North -Brabant border. This Waard was a reclaimed peat area with boundaries formed by the marshes bordering the Pleistocene deposits in the south, and for the rest by branches of the rivers Rhine and Meuse. The Waard was in those days the most important part of Holland. Two important cities, Dordrecht and Geertruidenberg, were situated within the limits of this area. Due to quarrels between the inhabitants, together with high gale floods, this part of Holland was seriously inundated (St. Elizabeth flood, 1421) and not reclaimed later on. The city of Dordrecht, which remained on a small island in the northwest, survived the catastrophe, and afterwards played an important role in the history of the Netherlands. Geertruidenberg in the south, however, declined to a dead town. The whole of the middle and western parts of the area became a bay of the sea (zeeboezem) like the Dollard, the Jade Bay and the Zuiderzee (fig. 2C). The Biesbosch bay, however, silted up rapidly due to very rich sediments supplied by the Rhine and the sea. This process, strongly influenced by some small fluctuations of the sea-level, is discussed. During the transgression phase a sidimentation pattern was produced in which only gradual transitions occur; this applies both horizontally and vertically. During the regression phase the increased river influence brought a much stronger contrast in the pattern of deposition. Gradually the new accretions of land were embanked, and this applies to most of them today. In the centre part of the area there are still some islands surrounded by tidal water courses and there is some foreland in different stages of development. In this area the four components of land use are: agriculture on the embanked islands, willow coppice plantations (photographs 2,6) and the culture of reeds (photographs 4,5) and rushes (photograph 3). Due to the peculiar habitat dominated by a fresh water tidal movement of two metre's amplitude this area is of foremost importance from a scientific (e. g. biological) point of view (fresh-water-tidal-delta). Although its scientific value will change, it will not be lessened, even if the tidal range is decreased in consequence of execution of the so-called Delta-scheme. Some of the existing dykes are not able to protect the land against high storm floods. A total embankment of the last remains of the bay is planned. There are some special difficulties concerning water conservancy that will not be discussed here. From a pedological point of view the area has a difficult structure, viz. at many places thin clay layers occur on sandy subsoils. Here drainage brings the danger of desiccation if no special measures are taken. Finally, a solution of the problem is proposed which meets the requirements of all interests concerned, i. e. agriculture, foreland plantations (reeds and willows) science, protection of nature and recreation.